Effect of Fringe Benefits and Remuneration on Employee Engagement: The Moderating Role of Perceived Organisational Support - Acheampong Evans OWUSU; Glover ESTHER; Takyi-Wadieh EBENEZER; Ampofo Anane KYEI (Journal of Human Resource Management, 2023)
Purpose of the Study - This study assessed the effect of fringe benefits and remuneration on employee engagement and explored the moderating role of perceived organisational support. Methodology- The study employed a quantitative approach in data collection and analysis. Data was collected through a structured questionnaire distributed among 270 employees from Asanduff Construction Limited- Accra, Ghana. The analysis was conducted using Partial Least Square Structural Equation Modelling. Findings- The study revealed that fringe benefits and remuneration had an effect on employee engagement. With the moderation analysis, perceived organisational support did not moderate the relationship between remuneration and employee engagement but moderated the relationship between fringe benefits and employee engagement. Limitations- First, the study’s limitation has to do with its geographical coverage. The study was also limited to the working staff of Asanduff Construction Limited with an estimated sample size of 278 which could be relatively small. Again, through questionnaires being used as the main instrument, the study responses might be without honesty and accuracy. Thus, the study results might be affected by bias which will limit the generalizability. An additional constraint of the study is its exclusive focus on a single company, thereby restricting the generalizability of the findings to the unique confines of that particular corporate culture. Practical implications- The results of this study will contribute to human resource managers’ efforts in putting plans in place to improve the operations of their companies. Line managers should therefore make every effort to ensure that their staff members perceive a positive and full support from the organisation in order to increase productivity, as this study emphasized on the importance of perceived organisational support. Strategically, leadership and management of organizations will base on the findings of this study and plan important workshops, seminars, symposiums, conferences etc. with a major focus on providing employees with proper fringe benefits at the workplace so as to ensure that they increase productivity at the workplace. Lastly, perceived organisational support which has been highlighted by literature needs to be existent at the workplace. By so doing employees will feel appreciated and will therefore be willing to commit their future to the good of the organisation through psychological meaningfulness Originality/value- The study contributes to literature by assessing the effect of fringe benefits and remuneration on employee performance and exploring the moderating role of perceived organisational support.